Insights: fear of GAD. Issue 2 (11th February 2021) - Wright, Duncan
Abstract : Welcome to Insights, a new series in which articles published in FEBS Open Bio are summarised for the wider community. We hope that this series will help make the findings we publish more accessible to the general public and encourage greater engagement. In this first article of the series, we introduce a research paper on fear in rats, authored by Professor Yuchio Yanagawa and colleagues and published in this issue. Photo: Young rat and cat in front of black background. Cynoclub/Shutterstock.com.